The role of diabetes mellitus and BMI in the surgical treatment of ankle fractures. Issue 2 (7th November 2017) - Lanzetti, Riccardo Maria; Lupariello, Domenico; Venditto, Teresa; Guzzini, Matteo; Ponzo, Antonio; De Carli, Angelo; Ferretti, Andrea
Abstract: Background: Open reduction and internal fixation is the standard treatment for displaced ankle fractures. However, the presence of comorbidities such as diabetes mellitus and body mass index (BMI) are associated with poor bone quality, and these factors may predict the development of postoperative complications. The study aim was to assess the role of diabetes mellitus and BMI in wound healing in patients younger than 65 years who were surgically treated for malleoli fractures. Methods: Ninety patients, aged from 18 to 65 years old, with surgically treated ankle fracture, were retrospectively enrolled. Patients were classified in two groups: patient with diabetes and patients without diabetes (insulin‐dependent and noninsulin dependent). All patients were assessed for wound complications, Visual Analogue Scale and Foot and Ankle Disability Index (FADI) were assessed for all patients. Logistic regression was used to identify the risk of wound complications after surgery using the following factors as explanatory variables: age, gender, duration of surgery, BMI, hypercholesterolemia, smoking history, diabetes mellitus, and high blood pressure. Results: In total, 38.9% of patients showed wound complications. Of them, 17.1% were nondiabetics and 82.9% were diabetics. We observed a significant association between DM and wound complications after surgery ( P  = .005). Logistic regression analysis revealed that DM ( P  < .001) and BMI ( P  = .03) were associated with wound complications. The odds of having a postoperative wound complication were increased 0.16 times in the presence of diabetes and 1.14 times for increasing BMI. Conclusion: This study showed that diabetes mellitus and higher BMI delay the wound healing and increase the complication rate in young adult patients with surgically treated bimalleolar fractures.